2021
DOI: 10.1111/hae.14451
|View full text |Cite
|
Sign up to set email alerts
|

Trends of outcomes and healthcare utilization following orthopaedic procedures in adults with haemophilia: A 3‐decade retrospective review

Abstract: Introduction Haemophilic arthropathy is a serious complication of haemophilia often requiring surgical intervention. It is unclear whether advances in comprehensive care are associated with a reduction in orthopaedic interventions and peri‐procedural resource utilization. Aim To determine temporal patterns of orthopaedic interventions in persons with haemophilia (PWH), and evaluate changes in healthcare utilization and outcomes. Methods In this Canadian multicentre retrospective cohort study, adult PWH from No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Excluding three studies, 24,28,30 the mean postoperative follow up period across the other 14 studies was 5.7 years (SD 5.0) with a range of .33 to 33.4 years.…”
Section: Results Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Excluding three studies, 24,28,30 the mean postoperative follow up period across the other 14 studies was 5.7 years (SD 5.0) with a range of .33 to 33.4 years.…”
Section: Results Synthesismentioning
confidence: 99%
“…A total of 17 eligible studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] were identified including two non-randomised interventional studies, 13 retrospective non-interventional studies and two case reports. Four of the noninterventional studies were comparative.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate intra- and postoperative care to avert postoperative residual contracture is needed in PWH [ 52 ]. In the last 30 years, there has been a decrease in the rate of TKA, probably indicating the impact of extensive utilization of tertiary hematological prophylaxis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%